#### Answer

$x_{1}=1$ and $x_{2}=-\dfrac{2}{3}$

#### Work Step by Step

$(x-1)(3x^2-x-2)=0$
$(x-1)(3x^2-3x+2x-2)=0$
$(x-1)[3x(x-1)+2(x-1)]=0$
$(x-1)(x-1)(3x+2)=0$
$(x-1)^2(3x+2)=0$
Therefore the solutions are $x_{1}=1$ and $x_{2}=-\dfrac{2}{3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$x_{1}=1$ and $x_{2}=-\dfrac{2}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.